One tool to find them all: a case of data integration and querying in a distributed LIMS platform. (30th January 2019) - Grand, Alberto; Geda, Emanuele; Mignone, Andrea; Bertotti, Andrea; Fiori, Alessandro
Abstract: In the last years, Laboratory Information Management Systems (LIMS) have been growing from mere inventory systems into increasingly comprehensive software platforms, spanning functionalities as diverse as data search, annotation and analysis. Our institution started in 2011 a LIMS project named the Laboratory Assistant Suite with the purpose of assisting researchers throughout all of their laboratory activities, providing graphical tools to support decision-making tasks and building complex analyses on integrated data. The modular architecture of the system exploits multiple databases with different technologies. To provide an efficient and easy tool for retrieving information of interest, we developed the Multi-Dimensional Data Manager (MDDM). By means of intuitive interfaces, scientists can execute complex queries without any knowledge of query languages or database structures, and easily integrate heterogeneous data stored in multiple databases. Together with the other software modules making up the platform, the MDDM has helped improve the overall quality of the data, substantially reduced the time spent with manual data entry and retrieval and ultimately broadened the spectrum of interconnections among the data, offering novel perspectives to the biomedical analysts.